Comparison of apixaban and rivaroxaban for anticoagulant effect after lumbar spine surgery: a single-center report - Zhang, Kun (Future Sci OA, 2018)
AIM: To compare efficacy and safety of anticoagulants apixaban and rivaroxaban after lumbar spine surgery retrospectively. METHODS: In this study comprising 480 patients, lower-limb swelling, deep venous thrombosis, pulmonary embolism, blood loss, ecchymosis and D-dimer changes were observed. RESULTS: The changes in perimeter of the legs were tested, and significant differences were noted 10 cm above the patella, but no significant differences 10 cm below the patella. Twelve thrombotic events occurred in the apixaban group and nine in rivaroxaban group. No significant difference in the incidences of thromboembolic events (p = 1.00). Compared with rivaroxaban, there was significantly less bleeding in the apixaban group (p = 0.03). CONCLUSION: Apixaban and rivaroxaban were equally effective anticoagulation therapies that exhibited similar preventive effects against postoperative venous thromboembolism after lumbar spine surgery.